On the Relationship between the Normal Incidence Airborne Sound-excited and the Structurally-excited Sound Radiation from a Wall: A Theoretical Trial with Simplified Models. Issue 2 (June 2015) - Yairi, Motoki; Sakagami, Kimihiro; Nishibara, Kosuke; Okuzono, Takeshi
Sound transmission and sound radiation by force excitation of a plate are both basic and important problems in acoustics. Both the sound transmission and force excited sound radiation are basically the same phenomena, i.e., sound radiation from a vibrating plate, and the difference is the type of the excitation force, i.e., surrounding sound field or mechanical force. However, their relationship has not been explicitly discussed. If the relationship is known, it should be useful for comprehensive understanding of those phenomena, and to gain insight into relevant problems. In this study, simplified theoretical analyses to find a possibility to obtain a relationship between the sound transmission and force-excited sound radiation of a sigle-leaf plate of infinite extent are carried out with simplified models. As a result, it is suggested that there is a conversion factor which relates the sound transmission and force-excited sound radiation, and its behavior is discussed through numerical examples. Even though the present analyses are approximated and simple, this result suggests that there is a possibility, with further sophisticated studies, for practical applications.